DAMPAK GENERASI Z SERTA KEPUTUSAN MENGGUNAKAN BSI MOBILE - Ulfa, Riski Walidaini; Djakfar, Inayatillah; Riza, Akmal (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2024)
This research aims to determine the influence of understanding products and service features on decisions Gen-Z to use BSI Mobile. Using quantitative methods with a descriptive approach, and the research sample was obtained 100 respondents using a cluster random sampling technique from Generation Z in Banda Aceh city who used BSI Mobile. Then, based on multiple linear regression analysis, the result were obtained that the variables of product understanding and service features had a positive and significant effect on the decision to use BSI Mobile.